Achieving group satisfaction in web-based learning: systematic-grouping method design. (24th April 2006) - Sun, Pei-Chen; Lee, Ching-Chang; Wang, Feng-Sheng; Lo, Ching-Hua
In a web-based learning environment, the instructor often faces a dilemma as to how to group learners in a short time and still satisfy their desire to be in a particular group. To resolve this situation, this paper proposes a systematic-grouping method in web-based learning. Experiments were conducted and results show that the proposed method can achieve better satisfaction levels and is less time-consuming.